Poverty and nutrition: A case study of rural households in Thailand and Viet Nam - Hermann Waibel; Lena Hohfeld (Asian Development Bank Institute (ADBI), 2016)
In this paper, we analyze the link between nutrition and poverty in two Asian countries where monetary-based poverty reduction was especially successful. Thailand and Viet Nam are two emerging market economies where poverty rates are now below 10% and are declining further. Despite this success, it is not clear to what extent this success has translated into similar improvements in the nutritional situation of the people and especially of children. We find that undernutrition continues to be a problem in Viet Nam with child underweight rates of 27% and therefore higher than headcount rates of the 1.25 poverty line. Also, Thailand, after the economic crisis, with 19% of children underweight, is still above the World Health Organization's threshold. We investigate the factors that influence nutrition outcomes, measured as Z-scores of the weight-for-age indicator, by using Tobit regressions for four different groups of children, based on income (poor vs. non-poor) and nutrition (underweight vs. non-underweight). We find that poverty and income influence nutrition outcomes, but other factors such as mother's height, education, migration and sanitation also affect nutrition. Coefficients of respective variables differ by poverty status. Our conclusion that non-monetary factors matter to reduce undernutrition, and, therefore, monetary poverty reduction is not a sufficient condition, is further underlined by a prediction of future undernutrition rates based on regressions. Also, we find that, even under the assumption of high growth, income growth alone will not be able to reduce undernutrition to a level of low severity until the year 2030.
Keywords: I31; I32; O10; 330; Poverty; nutrition; undernutrition; income growth; poverty reduction